Rare association of central pontine myelinolysis with intrasellar arachnoidocele - casual or correlated? - M.R. Cherkaoui Jaouad, MD; C. Amrani, MD; M. Mahi; N. Bouknani (Radiology Case Reports, 2022)
Our case report presents a patient with central pontine myelinolysis and arachnoidocele. He was hospitalized twice these 2 last months for a confusional syndrome associated to an alteration of his general health where metabolic disorders where found: a hyponatremia at 125 mmol/l that was quickly corrected and a hypoglycemia at 0.30 g/l. A central pontine myelinolysis was found as an iso-signal on T1-weighted sequences and a hypersignal on T2-weighted and FLAIR sequences on magnetic resonnance imaging. Central pontine myelinolysis lesions did not enhance with contrast. Incidental imaging findings of arachnoidocele was detected. Through this case, we would like to share with the other practitioners these rare images and the consequence of a diagnostic delay. Indeed, hyponatremia in our patient could be the consequence of the intrasellar arachnoidocele and the overly rapid correction of this chronic hyponatremia caused central pontine myelinolysis, or it is an accidental phenomenon where we found both lesions.